Квазіперіодичні вимушені коливання твердого тіла в полі квадратичного потенцiалу - Парасюк, I.О. (Нелінійні коливання, 2018)
Рассматривается натуральная лагранжева система, описывающая движение твердого тела
под действием суперпозиции двух потенциальных силовых полей. Первое поле стационарно и
имеет квадратичный потенциал, а потенциал второго — пространственно линеен и квазипериодически зависисит от времени. Установлены достаточные условия, при выполнении которых такая система имеет классическое гиперболическое квазипериодическое решение, локально минимизирующее усредненный по времени лагранжиан. The paper deals with a natural Lagrangian system which governs the motion of a rigid body under the action of superposition of two potential force fields. The first one is a stationary field with quadratic potential,
and the potential of the second one is space-linear and quasiperiodically dependend on time. We find
sufficient conditions under which such a system has a classical hyperbolic quasiperiodic solution locally
minimizing the time-averaged Lagrangian.